Supplementation Of Kencur (Kaempferia Galanga Linn) Extract on Malondealdehyde (MDA) and IL-6 Plasma Levels Post Aerobic Training Activity: Suplementasi Ekstrak Kencur (Kaempferia Galanga linn) terhadap Kadar Plasma Malondealdehide (MDA) dan Interleukin-6 (IL-6) Pasca Aktivitas Latihan Aerobik - Roy Januardi Irawan; Soni Sulistyarto; Nanda Rimawati (Universitas Airlangga, 2022)
Background: intense exercise causing an increase in substrate utilization by the working muscles, resulting in an increased use of oxygen. Increased oxygen consumption associated with activation of specific metabolic pathways due to exercise activity then triggers increased Reactive Oxygen Species (ROS) production. The increase in free radicals (ROS) can further cause cell damage. Kencur (kaempferia galanga) is a plant that is believed to have bioactive compounds, including phenolic compounds that have antioxidant activity. Objectives: The aim of this study was to determine the effectiveness of 15-days supplementation kencur (kaempferia galanga linn) on plasma MDA and IL-6 post aerobic exercise activity. Methods: This study was quasy experimental study, with a pretest - Post Test Control Group Design. A total of 30 Sports Science students of Universitas Negeri Surabaya who met the inclusion and exclusion criteria participated in this study. The participants divided into 2 groups, the kencur extract group (KG) of 200 mg/day and the placebo group (Pl). The supplementation was carried out for 15 days (14 days before and 1 day after aerobic exercise). Participants completed aerobic exercise (AE) consisting of 2x800 m with 2-minute intervals. Measurements of plasma MDA and IL-6 were 24 hours after AE. The difference test used repeated measures ANOVA with a significance level of P<0.05. Results: there was a significant difference in the plasma MDA and IL-6 between each group with the significance value of MDA was p = 0.000 and the significance value of Il-6 was p<0,001 Conclusions: Supplementation of kencur extract (Kaempferia Galanga Linn) for 15 days was effective to reduce the increase of oxidative stress (MDA) and the increase in pro-inflammatory cytokines (IL-6) after the implementation of aerobic exercise activities.